Analysis of the coexistence of conventional and unconventional credit markets in the agribusiness sector in Kenya - Philip Ngare (Kenya Bankers Association (KBA), 2019)
The study aims to examine reasons for agribusiness proprietors seeking unconventional loans, where conventional lenders offer loans at lower interest rates. Using cross-sectional data analysis, the study revealed the type of clients served by unconventional lending sector: Households that are excluded from conventional sector or (and) households that prefers unconventional loans because of lower transaction costs or lower risk. A unique modeling and statistical methods is developed to establish economies of scope enjoyed by unconventional lenders. Also, the study determined how best to measure and track agriculture-led economic transformation. Assess the role that inclusion of (women, youth), network data, plays in ensuring sustainable agriculture-led economic (transformation) growth and credit repayments. The study not only revealed that educational level is an important element that has a positive impact on agribusiness entrepreneur's demand for credit but also that if the conventional financial sector is subjected to repressive regulations by government, such as interest rate ceiling, which limit their capability and incentive of screening borrowers by designing credit contracts, the unconventional lenders will serve a larger credit market.
Keywords: C5; C8; 330; Agribusiness financing; Micro-credit; Market equilibrium; Multinomial logit regression